An outlook on the sustainable machining aspects of minimum quantity lubrication during processing of difficult to cut materials. (2020) - Singh, Gurpreet; Aggarwal, Vivek; Singh, Sehijpal
Abstract: Modern machining scenario is facing intense pressure to adopt sustainable machining to fulfill the demand of future energy need without compromising the reserve of conventional energy resources. The water crisis, energy deficit, global warming and profitability have generated the need of handsome debate on sustainable manufacturing in present scenario of industry 4.0. The technological development have raised the comfort level of living being with context to transportation, telecommunication and medical facilities as a result of processing harder grade materials utilizing conventional and modern machining operations. However, during processing of aforementioned materials the advanced level of process parameters require higher energy, consequently, resulted into elevated cutting temperature leading to poor product quality as well as uneconomical machining. Hence to lower the excessive cutting temperature the metal working fluids are utilized to absorb the heat evolved at different zones of machining operation. Consequently, the temperature get reduced, but raises the scarcity of negative effects such as skin rashes, itching, asthma, water pollution, soil pollution, mist generation and sometimes unprofitable conditions. So, to bridge the gap between the limitations of dry machining and conventional flood lubrication, the concept of minimum quantity lubrication has been exercised to achieve the challenges and goals of sustainable machining. In this papers, the sustainable machining aspects of minimum quantity lubrication has been while processing the titanium, Inconel, magnesium and other ferrous alloys which are widely used. The Investigation indicated that the sustainable machining is dominant in present era of machining employing minimum quantity lubrication, cryogenic cooling and other hybrid cooling methodologies. Furthermore, several technological advancements, such as UAG, ECT, UAM and LAM have been reported to ease conventional machining operations during processing of harder grades materials.